Polymorphous billiard as a new type of billiards with chaotic ray dynamics - Naydenov, S.V.; Maslovsky, Yu.N.; Yanovsky, V.V. (Вопросы атомной науки и техники, 2007)
A new type of chaotic billiards is introduced. Unlike the known ones, it contains scattering as well as focusing regions of the boundary and has no neutral components. The dumbbell-like from polymorphous billiards family is proposed. Its characteristic phase dynamics (at control parameter changes) is studied and Lyapunov exponent as well as invariant reflections density on the boundary are calculated. The chaotic behavior of the beams and their uniform stationary distribution are proved.